Letter from William Morris Davis to James Curtis Booth - Davis, William Morris (1862)
William Morris Davis (1815-1891), a member of the United States House of Representatives, writes to James Curtis Booth (1810-1888) regarding the coinage in New York and generally expressing his distaste of New York. Booth notes that he has replied with "reasons against in 6 pages."
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City